Potential development of field activity design on ecology material as student learning material - Rahmawati, Dini Nurani; Maftuha, Mahda Rizqina; Syahirah, St.; Saleh, Farhan Muharam; Jannah, Novi Dewi Khadikatul; Kusnadi, Kusnadi; Purwianingsih, Widi (Jurnal Mangifera Edu, 2025)
This study aims to analyze the design of laboratory activities (DKL) for field trips activities in the Ranca Upas heterogeneous forest and to provide solutions through reconstruction. The significance of using the field trip method to enhance student learning outcomes and environmental awareness. The Ranca Upas heterogeneous forest was chosen as a field trip location because it has high micro-diversity and abundance. The DKL was designed to examine the interaction between biotic and abiotic factors as well as the inter-component interactions in the heterogeneous forest. This study employed a qualitative descriptive method utilizing the Analyze, Create, Try, and Reconstruct framework. A survey of the forest locations served as the basis for developing the DKL. The design of the DKL was informed by the survey results and analyzed using the Novak-Gowin Vee Diagram rubric. A trial was conducted to assess the suitability of the DKL in real field conditions. The results of this trial were then analyzed, leading to a reconstruction of the DKL based on challenges encountered during the trial. The reconstruction process included refining the tools used, preparing more structured activity steps, and developing more comprehensive practicum questions. This research has implications for the development of higher-quality and more effective field trip DKLs, ultimately aimed at improving students' science process skills and critical thinking abilities.